Polish Surnames Ending in -owicz/-ewicz in the Anthroponymicon of Lutsk (Linguostylistic Studies, 2020)
The study of regional anthroponymy is one of the most relevant in modern linguistics. Surnames are considered mainly as a linguistic phenomenon in terms of linguistic and historical development, with a focus on their origin, surname appelative semantics, and specifics of name-formation patterns. The characteristic features of the economic, political, and cultural life of distant ancestors are elucidated via the case study of a surname origin. The author argues that specific features of the anthroponymic system may be associated with the linguistic interactions of those people who have been living in the same territory for a long time.The article analyzes the Polish surnames in -owicz/-ewicz of people who lived in Lutsk. They were selected from the metric books of the State Archives of Volyn region and act records of the birth at Lutsk City Council. The ethnic varieties of the anthroponymic material allow identifying the Polish and Polonized surnames involved in the analysis. They are created on the basis of the East Slavic lexemes with the Polish elements. Therefore, the emphasis is laid on the identification of the Polish vocabulary and, in particular, its specific phonetic and word-forming elements.It has been revealed that by its anthroponymy, the analyzed model represents mainly personal names (Deńkowicz, Jakubowicz) and appellations with personal (Niemiłowicz, Szczupłewicz) and non-personal meaning (Bażantowicz, Maskiewicz). The surnames of the people who live in Lutsk are the source pointing out the status of this or that family in the society officially identified since they explicitly reflect the time realities of the society in which they originated and functioned.
Keywords: anthroponym; Polish anthroponymy; suffix; surnames motivated by appelatives; the last names of nominal derivation